2004
DOI: 10.1159/000075316
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tyrosine Hydroxylase in Lymphocytes and Effect of Endogenous Catecholamines on Lymphocyte Function

Abstract: Objectives: To comprehend the changes and significance of the endogenous catecholamines in the immune system, we explored the synthesis of catecholamines by lymphocytes in various lymphoid organs and in different activated states, and the effect of the endogenous catecholamines synthesized by lymphocytes on the function of the lymphocytes themselves. Methods: Immunohistochemistry for lymphoid organs (mesenteric lymph nodes, spleen and thymus) and lymphocytes was used to observe their expression of tyrosine hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…1A). Other sources of NE could be found in the SVF of PVAT, such as macrophages (11), lymphocytes (58), and neurons. The catecholamines present in PVAT are releasable by tyramine and support contraction in the rat superior mesenteric artery independent of sympathetic innervation (5).…”
Section: Discussionmentioning
confidence: 99%
“…1A). Other sources of NE could be found in the SVF of PVAT, such as macrophages (11), lymphocytes (58), and neurons. The catecholamines present in PVAT are releasable by tyramine and support contraction in the rat superior mesenteric artery independent of sympathetic innervation (5).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that lymphocytes may express TH and can thus synthesize catecholamines, especially when activated (Qiu et al 2004). According to Kranz et al (1997), TH-specific immunoreactivity has been identified in thymic cortical epithelial cells of children, whereas only a few TH-positive cells have been found in the medulla.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, rat phagocytes were found to contain mRNA for both TH and DBH, which clearly were inducible by cell contact with bacterial lipopolysaccharide (LPS) (11). In parallel, rat lymphocytes (22,23) and human PBMCs (24) contain inducible mRNA for these catecholamine-generating enzymes, upregulation of which results in increased levels of dopamine, norepinephrine, and epinephrine when rat lymphocytes were stimulated (22). In contrast, pharmacological inhibition of TH and DBH in rat and human lymphocytes decreased intracellular catecholamine levels in a dose-dependent manner (22,25).…”
Section: Evidence For De Novo Synthesis Storage Release and Inactimentioning
confidence: 99%
“…However, it was not until the mid 1990s that it was reported that lymphocyte-derived catecholamines modulate lymphocyte functions in an autocrine and paracrine manner, providing these cells with a potent tool to fine tune their actions and crosstalk with nearby cells (13). Because the expression of TH and DBH mRNA has been found to be inducible by various stimuli when compared with non-stimulated lymphocytes, it seems likely that the catecholamine synthesis in lymphocytes and phagocytes depends on the functional state of these cells, and that there are diverse cell triggers (11,19,22,23). These auto-regulatory interactions between endogenous catecholamines and immune/ inflammatory cells can alter a wide array of cell functions, in part through adrenoceptors or dopaminergic receptors expressed on these cells (10,11,47,48) (see below).…”
Section: Modulation Of Immune/inflammatory Cell Functions By Catecholmentioning
confidence: 99%